ANALISIS PERBANDINGAN STRATEGI PEMASARAN DISTRO ESTIZY DAN DISTRO ALADDIN DI KOTA BIMA - Khaerul Rangga Kentari; Ita Purnama (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
This study uses a comparative method that is carried out on consumers who have shopped at the Estizy and Aladin Distro. The purpose of this study is to determine whether there are differences in the marketing strategy of the Estizy and Aladin Distro. Samples were taken as many as 100 people using a sampling technique, namely Proportioned Stratified random sampling. Data collection was carried out by distributing questionnaires. The analysis technique used the Paraid Sample T Test. The results showed that the Estizy and Aladin distributions were -1,926 with profitability or sig. (2-tailed) 0.060. Thus the value of t count <t table (-1.926 <1.984) and the value of profitability or sig. (2-tailed) 0.060 <0.05, then H0 is rejected (there is no significant difference). So it can be concluded that the Estizy and Aladdin distributions have differences that are not much different.